Women and Irrigation in Nepal: Context, Issues and Prospects - Ghimire, Sujan (Water Nepal, 2004)
In spite of the prevailing gender norms, which favour men, some legislation passed by the Nepali government acknowledges the role of Nepali women as irrigators. Policies which increase and strengthen women’s participation in the irrigation have been formulated. This article explores how these policies have been implemented and suggests measures which can be taken to further bolster women’s participation in this sector. Water Nepal Vol.11(2) 2004 pp.45-61